The effect of difference types of muffler on NA engine through experimental-flow / Mohd Fazli Abdul Rashid - Abdul Rashid, Mohd Fazli (2009)
Main function of muffler for IC engine is to provide noise silencing along with pollutant emissions compliance. It is equally important that these environmental objectives be achieved without significant impingement on the vehicle performance. A desirable exhaust system would have low weight and low backpressure for good engine performance and fuel economy, while providing low emission and sound levels. Modification on the muffler will help to improve its performance of engine. This project will focus on the effect of power, torque and air fuel, ratio by changing the muffler with two different size and flow. Experimental by using Hub Dynamometer was carried out in order to produce the result for Proton 1.6 engine. The result was compared to the standard engine in order to observation it effects.